Base temperature estimates for lisianthus cultivars grown in different planting seasons - Daniela Höhn; Roberta Marins Nogueira Peil; Priscila Monalisa Marchi; Paulo Roberto Grolli; Roberto Trentin; Willian Silveira Shaun (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to determine the base temperature of six lisianthus cultivars, grown at seven planting seasons in the municipality of Capão do Leão, in the state of Rio Grande do Sul, Brazil. The following cultivars were evaluated: DBL Echo Blue, Robella 2 Pink, Excalibur White, Excalibur 2 Blue Picotee, DBL Echo Champagne, and Arena III Red. Base temperature was determined from the air temperature data collected daily, in each planting season, fusing the lowest variability and development ratio methods. The base temperature for lisianthus cultivars is between 14.0 and 15.0ºC, by the lowest variability method, and between 13.9 and 15.0ºC by the development ratio method. The highest thermal accumulation was obseerved in the second planting season (from 11/23/2017 to 02/22/2018) for all cultivars, and lower air temperatures during the growing season resulted in longer production cycles. In the seven planting seasons, the highest base temperature is 15.0ºC, obtained for cultivar Arena III Red, and the is 14°C, for all lisianthus cultivars.